Computerized adaptive tutorials to improve and assess problem-solving skills - Nirmalakhandan, N. (Computers and education, 2007)
Recent research studies have reported on how novices and experts differ in storing, organizing, and retrieving subject matter knowledge and on how they apply their knowledge to solve new problems. These findings have been integrated and implemented in a computer environment to help novices improve their problem-solving skills. An outline of this implementation and the manner in which it is used in an undergraduate hydraulic engineering course are presented. Student feedback on the educational value of this approach as well as data to demonstrate the improvement in their problem-solving abilities are also included. Preliminary evidence supporting the validity of computerized assessment of problem-solving skills is also included.